BONE RECONSTRUCTION TECHNIQUES FOR DENTAL IMPLANT PROSTHETIC FIELDS: A META-ANALYSIS - Ioana Dobrovat; Tibeica Andreea; Haddad Clara Diana; Adam Eduard; Agop-Forna Doriana; Norina Forna (Romanian Journal of Medical and Dental Education)
Aim of the study: This study aims to evaluate the efficacy and safety of various bone reconstruction techniques for preparing the prosthetic field for dental implants.